Statistical Modelling of Oil Removal from Surfactant/Polymer Flooding Produced Water by Using Flotation Column - Ku Esyra Hani; Mohammed Abdalla Ayoub (Universitas Gadjah Mada, 2020)
The objective of this study was to investigate the effect of polymer (GLP-100) and surfactant (MFOMAX) towards the efficiency of oil removal in a flotation column by using the Response Surface Methodology (RSM). Various concentrations of surfactant (250, 372 and 500 ppm) and polymer (450, 670, and 900 ppm) produced water were prepared. Dulang crude oil was used in the experiments. Flotation operating parameters such as gas flow rate (1–3 L/min) and duration of flotation (2–10 min) were also investigated. The efficiency of oil removal was calculated based on the difference between the initial concentration of oil and the final concentration of oil after the flotation process. From the ANOVA analysis, it was found that the gas flow rate, surfactant concentration, and polymer concentration contributed significantly to the efficiency of oil removal. Extra experiments were conducted to verify the developed equation at a randomly selected point using 450 ppm of polymer concentration, 250 ppm of surfactant concentration, 3 L/min gas flowrate and duration of 10 min. From these extra experiments, a low standard deviation of 1.96 was discovered. From this value, it indicates that the equation can be used to predict the efficiency of oil removal in the presence of surfactant and polymer (SP) by using a laboratory flotation column.